A comparative study of serum cystatin C levels in Type 2 diabetes mellitus with and without microalbuminuria - Blessy Susan Luke; Anu C John (Asian Journal of Medical Sciences, 2023)
Background: Serum Cystatin C is elevated in diabetic patients even before the appearance of microalbuminuria and hence, it can be used as an early marker for detecting diabetic nephropathy. Aims and Objectives: The aim of the study was to compare serum Cystatin C levels in Type 2 diabetes mellitus (DM) patients with microalbuminuria and without microalbuminuria. Materials and Methods: A hospital-based and cross-sectional study conducted among 40 patients with Type 2 diabetic mellitus attending the Endocrinology OPD Medical College, Thiruvananthapuram. Informed consent was obtained. Biochemical parameters like blood glucose was estimated by hexokinase method and serum creatinine by modified Jaffe’s method using fully automated analyzer. HbA1c was determined by turbidimetric immunoinhibition method. Serum Cystatin C and microalbumin was evaluated by ELISA method. Statistical analysis of data was performed using SPSS windows version 26. Statistical tests like unpaired t-test were done to compare the study subjects and Pearson correlation was done to know the correlation between variables and P<0.05 was considered as significant. Results: In this study, all the study group had fasting blood level above 126 mg/dL with HbA1c value >6.5%. Serum creatinine value <1.4 mg/dL is considered normal. In this study group subjects, 34 (85%) had normal level of serum creatinine, while 6 (15%) 6 patients had creatinine level more than 1.4 mg/dL. Mean±SD for serum cystatin C levels in Type 2 DM patients with microalbuminuria and without microalbuminuria was 22.7±4.9 and 4.79±3.55, respectively. The serum cystatin C levels were significantly (P<0.01) higher in the microalbuminuria group than in the normoalbuminuric patients. In the present study, there was highly significant positive correlation between serum cystatin C and microalbumin (r=0.93, P<0.001. In the present study, there was highly significant positive correlation between serum cystatin C and fasting blood sugar, serum creatinine, and glycated hemoglobin in patients with microalbuminuria) than without microalbuminuria. Conclusion: Serum cystatin C levels were found to be increased in patients with Type 2 DM with microalbuminuria and can be considered as a valuable early marker of renal damage.